Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.9790/2380-07634042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Molecules for Management of Stem borers on Sugarcane

Abstract: An experiment was conducted at Regional Sugarcane and Rice Research Station, Rudrur during 2011 and 2012, to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…In a study conducted by Bhawar et al, (2016), Cartap hydrochloride was found effective in early shoot borer management in sugarcane while Thiodicarp was found ineffective. These findings are in line with the results of Pandey (2014) and Padmasri et al, (2014) who reported that Chlorantraniliprole 18.5 SC is the most effective insecticide against early shoot borer. In the same study, higher cane yield was found in Chlorantraniliprole 18.5 SC treated plots and high B: C ratio with Flubendiamide 39.35 SC and Spinosad 45SC treatments.…”
Section: Resultssupporting
confidence: 92%
“…In a study conducted by Bhawar et al, (2016), Cartap hydrochloride was found effective in early shoot borer management in sugarcane while Thiodicarp was found ineffective. These findings are in line with the results of Pandey (2014) and Padmasri et al, (2014) who reported that Chlorantraniliprole 18.5 SC is the most effective insecticide against early shoot borer. In the same study, higher cane yield was found in Chlorantraniliprole 18.5 SC treated plots and high B: C ratio with Flubendiamide 39.35 SC and Spinosad 45SC treatments.…”
Section: Resultssupporting
confidence: 92%
“…Sheeba Jasmine et al, (2012) and Gaje Singh et al, (2009) also postulated that rynaxpyr was most effective treatment recording the lowest incidence of sugarcane early shoot borer (15.43%). The present findings are in accordance with the results of Padmasri et al, 2014 as they have reported that, Chloranthriniliprole 18.5 SC @0.36 ml/l of water recorded the lowest per cent (11.07) early shoot borer incidence. The present findings are also in agreement with the observations of Singh et al, (2009) reported Rynaxypyr 20 Sc @100 g.a.i/ha was found to be the best with minimum of 0.12 per cent infestation by early shoot borer and gave maximum yield of 77.13 t/ha.…”
Section: B: C Ratiosupporting
confidence: 93%
“…However, Carbofuran 3G recorded the lowest cost: benefit ratio (1: 1.44) among the treatments (Table 5). Padmasri et al (2014) who reported high B:C ratio with Flubendiamide 39.35SC and Spinosad 45SC. Chlorantraniliprole 18.5 SC has the highest cost than all other test insecticides but it gave the maximum per cent reduction of early shoot borer.…”
Section: Resultsmentioning
confidence: 99%